Digitalni repozitorij Univerzitetne knjižnice Maribor - Bezget, Jan (Knjižnica, 2017)
Purpose: Paper presents a portal for browsing the University of Maribor Library (UML) digitised materials. The outline and contents design of the UML Digital Repository (DR UKM) as well as the software platform and the technical solutions are presented. The thematic collections for promotion of Maribor and Štajerska cultural heritage are emphasized. An emphasis is put on the presentation of the metadata scheme, in which the metadata for DR UKM are consistent with the COMARC/B format. Usage and licence information are also provided. The article stresses the repository's usability, as the digitised materials are available for different public and different purposes, like teaching, research or simply browsing. Methodology/approach: After examining good practice examples and due to the necessity of providing the UML materials also in digitised form, we decided to establish the DR UKM. An outline and contents design were prepared, collections to be digitised were selected, the software platform, the interface, and the metadata scheme, which enables connectivity with other systems in open access, were prepared. Results: A portal for browsing the UML digitised materials with the emphasis on open access to cultural heritage, which can be connected to other digital repositories, was established. With the DR UKM the UML contributes to shaping the virtual world of knowledge; with digitising precious cultural heritage of the university, the city and the region it ensures a wide access to cultural goods. Originality/practical implications: The DR UKM was built by the University of Maribor professionals' own knowledge. It offers a wider accessibility and it protects rare and antiquarian materials 24/7; it also enables cooperation among libraries on the national and local level. Exchange of information and digitised objects as well as their searching are simplified.
Keywords: cultural heritage; digital archives; digital collections; digitalizacija; digitalne zbirke; digitalni arhivi; Digitalni repozitorij UKM; kulturna dediščina; management; UML Digital Repository; University of Maribor Library; Univerzitetna knjižnica Maribor; upravljanje